Multicenter analysis of the use of transjugular intrahepatic portosystemic shunt for management of MPN‐associated portal hypertension. Issue 9 (26th July 2017) - Reilly, Christopher R.; Babushok, Daria V.; Martin, Karlyn; Spivak, Jerry L.; Streiff, Michael; Bahirwani, Ranjeeta; Mondschein, Jeffrey; Stein, Brady; Moliterno, Alison; Hexner, Elizabeth O.
Abstract: BCR‐ABL1 ‐negative myeloproliferative neoplasms (MPNs) are clonal stem cell disorders defined by proliferation of one or more myeloid lineages, and carry an increased risk of vascular events and progression to myelofibrosis and leukemia. Portal hypertension (pHTN) occurs in 7‐18% of MPN patients via both thrombotic and nonthrombotic mechanisms and portends a poor prognosis. Transjugular intrahepatic portosystemic shunt (TIPS) has been used in the management of MPN‐associated pHTN; however, data on long‐term outcomes of TIPS in this setting is limited and the optimal management of medically refractory MPN‐associated pHTN is not known. In order to assess the efficacy and long‐term outcomes of TIPS in MPN‐associated pHTN, we performed a retrospective analysis of 29 MPN patients who underwent TIPS at three academic medical centers between 1997 and 2016. The majority of patients experienced complete clinical resolution of pHTN and its clinical sequelae following TIPS. One, two, three, and four‐year overall survival post‐TIPS was 96.4%, 92.3%, 84.6%, and 71.4%, respectively. However, despite therapeutic anticoagulation, in‐stent thrombosis occurred in 31.0% of patients after TIPS, necessitating additional interventions. In conclusion, TIPS can be an effective intervention for MPN‐associated pHTN regardless of etiology. However, TIPS thrombosis is a frequent complication in the MPN population and indefinite anticoagulation post‐TIPS should be considered.